2013
DOI: 10.1371/journal.pone.0077893
|View full text |Cite
|
Sign up to set email alerts
|

Lactobacilli Regulate Staphylococcus aureus 161:2-Induced Pro-Inflammatory T-Cell Responses In Vitro

Abstract: There seems to be a correlation between early gut microbiota composition and postnatal immune development. Alteration in the microbial composition early in life has been associated with immune mediated diseases, such as autoimmunity and allergy. We have previously observed associations between the presence of lactobacilli and Staphylococcus (S.) aureus in the early-life gut microbiota, cytokine responses and allergy development in children. Consistent with the objective to understand how bacteria modulate the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 45 publications
1
24
0
Order By: Relevance
“…While an early-life gut microbiota positive for lactobacilli was associated with a regulated immunological profile and protection against allergy development in children, early colonization with S. aureus was associated with strong in vitro immune responses, particularly when lactobacilli were not detected. These associations between in vivo colonization and immune responsiveness in vitro have been confirmed in further studies-and we have observed that while different lactobacilli (e.g., Lactobacillus [L.] reuteri and L. rhamnosus) readily activate innate immune cells like monocytes, they are capable of dampening S. aureusinduced immune activation of adaptive immune cells like T cells in vitro [22]. Recently, we have also shown that L. reuteri has a significant impact on (the maturation of) both conventional and retinoic acid-derived DC in making them less responsive to an inflammatory challenge [23].…”
Section: Introductionsupporting
confidence: 79%
See 3 more Smart Citations
“…While an early-life gut microbiota positive for lactobacilli was associated with a regulated immunological profile and protection against allergy development in children, early colonization with S. aureus was associated with strong in vitro immune responses, particularly when lactobacilli were not detected. These associations between in vivo colonization and immune responsiveness in vitro have been confirmed in further studies-and we have observed that while different lactobacilli (e.g., Lactobacillus [L.] reuteri and L. rhamnosus) readily activate innate immune cells like monocytes, they are capable of dampening S. aureusinduced immune activation of adaptive immune cells like T cells in vitro [22]. Recently, we have also shown that L. reuteri has a significant impact on (the maturation of) both conventional and retinoic acid-derived DC in making them less responsive to an inflammatory challenge [23].…”
Section: Introductionsupporting
confidence: 79%
“…In our model, it is likely that SE have bound MHC on the DC that are capable of activating T cells, even though the CFS was added just once at day 3 of DC generation and that substantial washing of the DC was performed before co‐culture. However, we have previously shown that this S. aureus ‐CFS induces inflammatory responses by intestinal epithelial cells, which might indicate its potential to use other mechanisms to activate cells than via the obvious MHC–TCR interaction .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Many researchers have understood that the surface microflora affects the innate and adaptive immune system. The beneficial effect of microflora in the gastrointestinal tract supports the use of probiotic [17]. Probiotic in the process of wound healing has been used by the researchers with the promising result [18], [19].…”
Section: Resultsmentioning
confidence: 99%